(untitled) (Research, Society and Development, 2022)
The choice of species for the recovery of degraded areas in riparian forests is of paramount importance. Therefore, aspects such as the plasticity of the species in relation to different environments and the availability of seedlings for long periods must be taken into account. In this way, cloning meets these aspects, and can be the solution in the production of quality seedlings throughout the year. Therefore, the objective of this work was to verify the rooting and survival of cuttings of Ochroma pyramidale (Cav.) Urb. in parent plants at different ages. To carry out the experiment, 64 cuttings were prepared, all with a bevel cut and half of their leaves cut and after this procedure they were planted in a commercial substrate bed in a drained polyethylene tray, measuring 70 cm x 70 cm and sealed at the top with plastic film. The evaluation took place after 46 days, where the percentage of rooting, survival and mortality were evaluated. The design used was completely randomized and the data were submitted to analysis of variance and the means were compared by Tukey’s test, using the software R 3.4.0. There was an average rooting rate of 25% in the cuttings, and in the cuttings of PM1, PM2 and PM3, aged between 270 and 150 days, they showed rooting capacity; while PM4 had no rooted cuttings. The rooting accounted for by matrices was as follows: PM1 (50%), PM2 (18.75%) PM3 (31.25%) and PM4 (0%). Cuttings with greater chronological age and greater diameter in our study had a higher percentage of rooting, which may be related to their lignification. The species O. pyramidale shows potential for clonal garden preparation by cuttings with 25% rooted cuttings and 60.9% survival without the use of phytoregulators.